REAKSI PASAR MODAL DI INDONESIA, KOREA SELATAN, DAN AMERIKA SERIKAT TERHADAP BERITA VIRAL - Devi, Pande Paramitha; Wiguna, Atu Bagus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research has purpose to determine abnormal returns around the event date and market reactions in South Korea, the United States and Indonesia to news that is currently viral. Expected return is calculated using the market-adjusted model. The estimation period used in this study is 5 days before the announcement, at the time of the announcement, and 5 days after the announcement. The sample used was 57 companies in the entertainment, movies and media (EMM) sector. This research method uses a one sample t test and ANOVA. The results of the study found that there were significant differences in abnormal returns before, during, and after the release of viral news in South Korea and the United States and there were reactions in the South Korean and United States stock markets to viral news. While in Indonesia there are no significant differences in abnormal returns before, during, and after the release of viral news and there is no market reaction to viral news.